Sustainable potassium-doped graphene oxide from oak fruit agricultural waste for a synergistically improved nanofluid-surfactant slug for enhancing oil recovery - Pandey, Anurag; Tewari, Chetna; Yadav, Shivam; Kesarwani, Himanshu; Saxena, Amit; Sharma, Shivanjali; Jung, Yong Chae; Sahoo, Nanda Gopal (Elsevier BV, 2024)
This study presents an eco-friendly solvothermal method for synthesizing potassium-doped graphene oxide (KGO) from agricultural waste, specifically oak fruit. Various spectrographic analyses, including XRD, FTIR, Raman, and UV-Vis, confirmed the successful synthesis of graphene oxide. The synthesized K-GO was combined with different surfactants to create nanofluids to enhance oil recovery. Anionic sodium dodecyl sulfate (SDS) demonstrated the best performance among the surfactants tested. When 250 ppm of K-GO was added to a 2500 ppm SDS solution, the surface tension was reduced by over 10 %. The study of zeta potential experiments validated that the K-GO-SDS nanofluid is compatible with sandstone reservoirs. Furthermore, the interfacial tension between the K-GO-SDS nanofluid and crude oil decreased by approximately 40 %. Batch adsorption studies showed that the combination of SDS and K-GO significantly reduced surfactant loss to reservoir surfaces by up to 32 %. Additionally, incorporating K-GO resulted in a notable improvement in wettability alteration, with contact angle measurements showing an improvement of over 20 degrees. The sustainable synthesis of potassiumdoped graphene oxide (K-GO) facilitates synergistic interactions with sodium dodecyl sulfate (SDS), thereby optimizing the formulation of nanofluids for enhanced oil recovery applications. This combination demonstrates superior efficacy in accessing trapped oil compared to using surfactants alone, highlighting the significant potential of K-GO-SDS nanofluids in advancing oil recovery techniques.